Analysis of Moderation Values in Buddhist Education Textbooks for Indonesian High Schools - Sujata, Dian Tika; Encep Syarief Nurdin; Komalasari, Kokom; Dahliyana, Asep; Siswantara, Yusuf (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2025)
This study examines how Buddhist Religious Education and Character-Building textbooks for Indonesian senior high schools under the Merdeka Curriculum represent religious moderation values. While previous research has extensively analyzed Islamic religious education textbooks, Buddhist textbooks remain unexplored, representing a significant gap in Indonesian academic literature. Using qualitative content analysis, this study analyzes Buddhist religious education textbooks for grades X, XI, XII, examining textual, visual, and multimodal elements through the Ministry of Religious Affairs' four indicators: tolerance, anti-violence, local culture acceptance, and national commitment, and employing Sadker and Zittleman's framework to identify bias. Findings reveal that textbooks systematically integrate moderation values through Buddhist teachings such as the Kalama Sutta, historical narratives of Buddhist-Hindu coexistence, cross-sectarian inspirational figures, and integration with Pancasila national ideology. Tolerance is operationalized as critical praxis combining openness with evaluative rationality rather than passive acceptance. However, three systematic biases were identified: religious invisibility through exclusion of belief systems and other religions beyond six officially recognized religions, imbalance in presenting inter-sectarian differences limited to symbolic aspects without philosophical depth, and cosmetic bias where student activities lack adequate textual scaffolding. This study makes a unique contribution by filling the gap in Buddhist religious education textbook analysis in Indonesia and demonstrating that while Buddhist textbooks show progressivity in representing moderation values, structural improvements in comprehensiveness, philosophical depth, and inclusive representation are essential for developing genuine cross-cultural religious literacy and supporting Indonesia's pluralistic educational goals.